From Reading to Writing: The Effect of a Gamified Mini-Story Application on Elementary Students’ Writing Skills - Barokah Widuroyekti; Hadiqotul Luluk; Arifin Nur Budiono; Yurike Kinanthy Karamoy (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Elementary students often find it difficult to transform ideas gained from reading into coherent written stories. This study examined the effectiveness of the gamified Baca dan Tulis Cerita Mini application in supporting third-grade students’ mini-story writing skills and described its classroom implementation. A quantitative quasi-experimental study was conducted using a pretest–posttest non-equivalent control group design with 56 students from MIMA KH. 01 KH. Shiddiq, Jember, Indonesia. Twenty-eight students participated in the experimental group and learned through the gamified application, while 28 students in the control group received conventional instruction. Students’ writing was assessed using an analytic rubric covering content relevance, story structure, coherence, vocabulary, sentence accuracy, and creativity. Data were analysed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s test, paired-samples t-test, and independent-samples t-test. The experimental group’s mean writing score increased from 72.11 to 95.11, whereas the control group improved from 71.14 to 76.46. The within-group analysis showed significant improvement in the experimental group, t(27) = −30.858, p < .001, while the posttest comparison also indicated a significant difference between groups, t(54) = 29.612, p < .001. Classroom observations indicated that students generally followed the application sequence after initial guidance and remained involved in the learning activities. The findings suggest that integrating model reading, guided activities, and gamified progression can support elementary students in developing more structured, coherent, and creative mini-stories.